PENGARUH INVESTASI DAN TENAGA KERJA TERHADAP PDRB SEKTOR INDUSTRI DI PROVINSI JAWA BARAT - Mikha Lola Melyani Silaen; Astrid Maria Esther (Media Ekonomi, 2015)
This research aims to understand how the influence of the investment and labor against the economic growth of industrial sector in the Province of West Java. The analysis technique which use in this research is regretion of panel data analysis. The data which use is GDP (Gross Domestic Product) industry sector, investment industrial sector, and the number of labors in the industrial sector from 2009 to 2013. This data consists of time series data (2009-2013) and cross section data (25 cities / regencies in West Java Province). Based on the analysis of panel data, the variable of investment and variable of labor have positive and significant impact on economic growth in the industrial sector in the Province of West Java.